Sexually fertile Magnaporthe grisea rice pathogens in Thailand - Mekwatanakarn, Poonsak; Kositratana, Wichai; Phromraksa, Tawatchai; Zeigler, R.S. (Scientific Societies, 1999)
Sexual fertility and mating type distribution of Magnaporthe grisea field isolates collected in Thailand were analyzed from sites previously found to harbor diverse populations of the pathogen. Three hundred forty-one single conidium isolates of M. grisea collected from five sites in north, northeast, and central Thailand were evaluated for in vitro sexual fertility and mating type by pairing with strains of known mating type. Most isolates (67%) were infertile when crossed with the hermaphrodite tester strains; but fertile isolates of each mating type that yielded viable ascospores were detected in all sites from the northeastern and northern regions. MAT1-2 predominated over MAT1-1 in bioassay mating type. Male fertility (female sterility) predominated in fertile MAT1-1 (50 to 75%) and MAT1-2 (50 to 85%) isolates from all locations in Thailand; however, hermaphroditic and/or female fertile isolates were also detected in all but one site. Fertility, as determined by perithecia density, was low (<10 perithecia cm-2) for most isolates, although a few produced in excess of 20 perithecia cm-2.